STUDI ANALISIS SETTING FILTER AKTIF TERHADAP PENINGKATAN KUALITAS DAYA LISTRIK DI GEDUNG PERKULIAHAN FAKULTAS TEKNIK UNIVERSITAS UDAYANA JALAN PB SUDIRMAN - Yogadipha Bagas, I Gede Dyotha; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2020)
Harmonics are disturbances in the electric power system in the form of distortions in current and voltage waves caused by the formation of waves with a interger multiplied frequency of the fundamental frequency. Total Harmonic Distortion (THD) is the amount of the effective value of waves affected by harmonics that affect the occurrence of electrical power losses. This study discusses the analysis of current THD in the lecture building at the Faculty of Engineering, Udayana University, Jalan PB Sudirman. The simulation is carried out under existing conditions and when operating an active filter will show the results of the THD current then adjusted to the IEEE 519-2014 standard. Then an analysis of power losses due to harmonics is performed. THDi in the existing conditions for phase R = 15.44%, S = 15.6%, and T = 11.42% while the active filter operation is at phase R = 2.41%, S = 2.69%, and T = 2.99%. Power losses due to haronisa interference under existing conditions were 12,6 % and on the active filter operating conditions were 0,037 %.